The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fcimb.2021.708325
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transducer and Activator of Transcription-3 Modulation of Cardiac Pathology in Chronic Chagasic Cardiomyopathy

Abstract: Chronic Chagasic cardiomyopathy (CCC) is a severe clinical manifestation that develops in 30%–40% of individuals chronically infected with the protozoal parasite Trypanosoma cruzi and is thus an important public health problem. Parasite persistence during chronic infection drives pathologic changes in the heart, including myocardial inflammation and progressive fibrosis, that contribute to clinical disease. Clinical manifestations of CCC span a range of symptoms, including cardiac arrhythmias, thromboembolic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 75 publications
(117 reference statements)
2
21
1
Order By: Relevance
“…1B ). Other studies suggested that disruption of IL-6 expression and downstream targets during parasite infection play important roles in T. cruzi pathogenesis ( 5 6 7 47 ). These results suggest that these piRNAs may be important modulators of IL6 and SOCS3 gene expression during the early/acute phase of T. cruzi infection and pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1B ). Other studies suggested that disruption of IL-6 expression and downstream targets during parasite infection play important roles in T. cruzi pathogenesis ( 5 6 7 47 ). These results suggest that these piRNAs may be important modulators of IL6 and SOCS3 gene expression during the early/acute phase of T. cruzi infection and pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Since the IL-6 pathway has been shown to be important in T. cruzi pathogenesis ( 6 47 ), we decided to evaluate the expression of those piRNAs in T. cruzi challenged PHCF because their differential expression could be context dependent ( 41 42 43 ). To evaluate the expression of IL6 , SOCS3 , and the piRNAs of interest that can target them, we challenged PHCF with T. cruzi trypomastigotes for various time points (0, 1, 3, and 6 h), and extracted total and small RNAs for our RT-qPCR assays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, vaccines are unavailable, and there are no alternative treatment options currently available. Therefore, strategies or potential drugs are highly desirable to diminish inflammation and fibrosis during the infection (18).…”
Section: Introductionmentioning
confidence: 99%